2021
DOI: 10.3390/molecules26030526
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyfluorinated Thia- and Oxathiacalixarenes Based on Perfluoro-m-xylene

Abstract: Perfluorinated tetrathiacalix[4]arene was obtained by heating perfluoro-m-xylene with thiourea or 2,5-difluoro-4,6-bis(trifluoromethyl)benzene-1,3-dithiol at 90 °C. Interaction of perfluoro-m-xylene with resorcinol or orcinol under mild conditions and subsequent heating of the mixture with 2,5-difluoro-4,6-bis(trifluoromethyl)benzene-1,3-dithiol leads to polyfluorinated dioxadithiacalix[4]arenes. Triphenyl and pentaphenyl ethers formed by the interaction of perfluoro-m-xylene with resorcinol under heating with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…In a perfluoropolyaromatic compound, substitution may occur at one position preferentially. According to experimental data and theoretical calculations [ 80 ], the main S N Ar sites for PFT and PFX are ortho- and para-positions towards the CF 3 group [ 79 , 81 ]. Previously, we found that the reaction of HTL with PFT occurs in para position.…”
Section: Resultsmentioning
confidence: 99%
“…In a perfluoropolyaromatic compound, substitution may occur at one position preferentially. According to experimental data and theoretical calculations [ 80 ], the main S N Ar sites for PFT and PFX are ortho- and para-positions towards the CF 3 group [ 79 , 81 ]. Previously, we found that the reaction of HTL with PFT occurs in para position.…”
Section: Resultsmentioning
confidence: 99%